Mother's knowledge and attitude in providing balanced nutrition with efforts to prevent undernutrition in toddler (3-5 years) - Maria Haryanti Butarbutar; Joko Prasetyo; Indasah Indasah (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background: Food eaten can used in a manner good for the body is contains nutrition. Frequent nutrition is used for the needs body like carbohydrates proteins, fats, vitamins, minerals, and water. In 2019 numbers national stunting prevalence to 27 .67. Whereas in 2020 numbers prevalence national to 24.1. The level of the mother's knowledge about nutrition is very important in increasing the degree of the family's nutritional status, especially the nutritional status of children because the role of the mother is very influential. Parents have an important role in fulfilling the nutrition of toddlers because toddlers still require special attention in their development, more particularly the role of a mother as the figure most often together with toddlersObjective: Research conducted to know and describe the connection between knowledge and attitude mothers in gift nutrition balanced with effort prevention nutrition not enough on toddlers. Methods: This type of research is quantitative and with explanatory surveys or interviews. The research design was cross-sectional, namely, the steps involved in collecting data and using a questionnaire given to respondents. The research sample was taken by using a simple random sampling method. Respondents in this study were mothers who had children aged 3-5 years as many as 83 people using the chi square test. Results:  The research that has been carried out is based on maternal knowledge with a p-value of 0.009 and maternal attitudes with a p-value of 0.015.Conclusion: The research that has been studied based on knowledge and attitudes with the results of Ha is accepted, meaning that there is a relationship between balanced nutrition and efforts to prevent undernutrition in toddlers. Providing balanced nutrition with efforts to prevent undernutrition in toddlers. Balanced nutrition is the food and needs that are eaten and consumed in balance with the needs of the body with a variety of foods if the mother has knowledge then the provision of balanced nutrition can be carried out and supported by good education, the mother's knowledge will be good and the results obtained will be good, but due to the education of mothers, there are still those who have graduated from elementary school, junior high school, and mothers do not know how to provide a variety of foods that suit the needs of toddlers so that the food consumed is still lacking to prevent malnutrition from occurring to toddlers.